Optimal District Metered Area design by Simulated Annealing - Gomes, Ricardo (2020)
Water losses reduction in Water Distribution Systems (WDS) is nowadays an issue of growing importance for water companies to ensure the sustainability of these public services. In this context, the implementation of District Metered Areas (DMAs) and/or pressure management are considered the most effective tools for leakage control, particularly in large networks and in systems with deteriorated infrastructures and with high pressure. Based in previous studies performed by the authors [1,2,3], the methodology described in this paper follows the ‘water losses management international best practices’ and makes it possible to evaluate the Net Present Value (NPV) of DMAs project, as well as the benefits that can be achieved by pressure management in WDS, particularly in terms of water production reduction. It is based on the analysis of the minimum night flow and the FAVAD concept, and it uses a pressure driven simulation model to predict the network hydraulic behaviour under different pressure conditions. Leakage assessment is performed using pressure driven analysis and the optimal location of pipes reinforcement/replacement and settings of the Pressure Reduction Valves (PRVs) are identified by a Simulated Annealing algorithm. The potential of this methodology is illustrated through an hypothetical case study.